Genetics and Genomics of Longitudinal Lung Function Patterns in Individuals with Asthma - Yates, Katherine P. (2017)
Rationale: Patterns of longitudinal lung function growth and decline in childhood asthma have been shown to be important in determining risk for future respiratory ailments including chronic airway obstruction and chronic obstructive pulmonary disease. Objectives: To determine the genetic underpinnings of lung function patterns in subjects with childhood asthma. Methods: We performed a genome-wide association study of 581 non-Hispanic white individuals with asthma that were previously classified by patterns of lung function growth and decline (normal growth, normal growth with early decline, reduced growth, and reduced growth with early decline). The strongest association was also measured in two additional cohorts: a small asthma cohort and a large chronic obstructive pulmonary disease metaanalysis cohort. Interaction between the genomic region encompassing the most strongly associated single-nucleotide polymorphism and nearby genes was assessed by two chromosome conformation capture assays. Conclusions: Early decline in lung function after normal growth is associated with a genetic polymorphism that may also protect against early decline in reduced growth groups.